The effects of bentonite on egg performance of laying hens - INAL, F; GULSEN, N; COSKUN, B; ARSLAN, C (The Indian Journal of Animal Sciences, 2013)
The experiment was conducted to evaluate the effects of bentonite on egg production, egg weight, egg specific gravity, feed consumption and feed efficiency of laying hens. Babcock Brown laying hens at 32 weeks of age were fed diets containing 0 (control), 1.5,2.5, and 3.5% bentonite for 3 months. Egg yield was not affected by bentonite. Damaged egg rates (broken plus abnormal size) decreased by feeding 1.5 and 2.5% bentonite, whereas 3.5% did not have any effect. Egg weight 61.42, 61.15, 61.21 and 60,41 g of experimental groups respectively. Both egg weight and egg specific gravity were not influenced by bentonite. Feed efficiency (kg feed/kg egg) was 2.47, 2.45,2.43 and 2.59 in the groups fed 0, 1.5,2.5, and 3.5% bentonite respectively.